P10 Interactions of fibroblasts derived from irradiated subcutaneous connective tissue with HNSCC. Issue 5 (May 2015) - Gehrke, T.; Hackenberg, S.; Scherzad, A.; Kleinsasser, N.
<x xml:space="preserve">Abstract</x> Introduction Cancer cells show a variety of interactions with cells of the surrounding connective tissue, mainly consisting of fibroblasts. Human skin-fibroblasts which are co-cultivated with tumor cells have the ability to convert into carcinoma-associated fibroblasts (CAF's) which are known to support tumor growth and invasiveness. The aim of the current study was to determine the impact of irradiation on fibroblast-tumor interaction. Material Primary human fibroblasts of subcutaneous connective tissue of pre-irradiated or non-irradiated skin were co-cultivated with the HNSCC cell line FaDu for 3 days. MTT assay, annexin V-propidium iodide test and ELISA were performed to analyze tumor viability, apoptosis and secretion of interleukin (IL)-6 and IL-8. Markers for epithelial-mesenchymal transition (EMT) were assessed by western blot. Results Co-culture with pre-irradiated fibroblasts showed a significant decrease in tumor viability and an increase in apoptosis. Levels of IL-8 significantly decreased in irradiated compared to non-irradiated fibroblasts. After irradiation, the cells did not promote EMT anymore. Conclusion Previous radiation influences fundamental properties of the complex tumor and stroma orchestration. These interactions have to be evaluated in detail in order to further illuminate possible options of intervention.